CONGENITAL HEART DISEASE IN CHILDREN AND ADULTSThe emotional reactions of parents to the hospitalization and conservative treatment of children after cardiac surgery in comparison to the parents of children treated for acute infection - Stochel-Gaudyn, Anna; Składzień, Tomasz; Skalski, Janusz Hieronim; Fyderek, Krzysztof (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Background : Hospitalization of children is a highly stressful situation for their parents, related to the feeling of danger and uncertainty, which can affect family functioning. Aim of the study: The aim of this study was to assess the emotional reactions of parents to the hospitalization of their children, as well as to evaluate the differences in these reactions between parents of children after cardiac surgery versus parents of children suffering from acute infection. Material and methods: The study population consisted of 140 parents (114 mothers, 26 fathers) of children hospitalized and treated conservatively in the Polish-American Institute of Pediatrics of the Jagiellonian University in Kraków in 2010 and 2011. The modified HADS scale (Hospital Anxiety and Depression Scale) was used for the assessment of parental emotional reaction. Examining the levels of anxiety, depression, and aggression (irritability), it was originally developed by Snaith and Zigmond; its modified Polish version was prepared by M. Majkowicz, K. de Walden-Gałuszko, and G, Chojnacka-Szawłowska. Results: In the examined group, a high level of anxiety was exhibited by 60 (78.9%) parents of children after cardiac surgery (subgroup I) vs. 13 (20.3%) parents of children with acute infection (subgroup II). Conclusions : The hospitalization of a child and the undertaken medical procedures form a highly stressful situation for the parents, which can increase their levels of anxiety, depression, irritability, or even aggression.